Field and laboratory studies to determine the suitability of Cissoanthonomus tuberculipennis (Coleoptera: Curculionidae) for release against Cardiospermum grandiflorum (Sapindaceae) in South Africa - Simelane, David (2014)
Cardiospermum grandiflorum is an invasive creeper that was targeted for biological control in South Africa in 2003. To determine ecological host range of its natural enemies, surveys were conducted on C. grandiflorum and 11 other Sapindaceae at 40 sites in the weed?s native range (Argentina). These surveys indicated that the seed-feeding weevil Cissoanthonomus tuberculipennis was restricted to C. grandiflorum, and that it was among the common natural enemies, occurring at most sites where C. grandiflorum was recorded. Open-field tests were conducted under natural conditions in Argentina to determine the host preference of C. tuberculipennis and other natural enemies of C. grandiflorum among three Cardiospermum species. These tests revealed that C. tuberculipennis and the bug Gargaphia sp. were restricted to C. grandiflorum though the latter subsequently developed on non-target Cardiospermum species in the laboratory. C. tuberculi- pennis was found to be highly damaging, destroying up to 44% of the seeds per plant in Argentina. In all the host-specificity tests, including no-choice, paired- choice and multi-choice tests, C. tuberculipennis only fed and developed on C. grandiflorum. Failure of C. tuberculipennis to feed and develop on all congeners of C. grandiflorum shows that the weevil is highly host-specific to the target weed. Results of host-specificity tests, open field tests and long-term monitoring of C. tuberculipennis populations demonstrate that the weevil poses no threat to non- target plant species, and therefore safe for release against C. grandiflorum in South Africa. Permission to release C. tuberculipennis in South Africa has been granted by the relevant regulatory authorities.